Budi Daya Tanaman Bengkuang (Pachyrhizus erosus L.) di Kelurahan Situgede, Kota Bogor - Muhammad Raihan Ferdiansyah; Edi Santosa (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2020)
Yam bean is important product in Bogor for fresh consumption and fermented food. However, evaluation on yam bean production is rare in Bogor. The application of good cultivation techniques is important in order to produce optimal yield to meet market demands. The study aimed to evaluate the cultivation system applied by farmers in Situgede Village, Bogor, West Java. Data were collected through interviews, field observations, and literature review. Based on interviews and field observations, there were variation among farmers in plant spacing, land area, type of fertilizer used, and productivity. Farmers still faced lack of skill on good cultivation techniques in order to obtain optimum productivity, as well as lack of information from experts in the field on cultivation method and plant diseases so that determined the effectiveness in yam cultivation. Keywords: cultivation, cultivation evaluation, plant diseases, plant spacing, yam bean